Competence and Motivation Analysis on Work Performance: Empirical Study of Military Institution - Liswinda, Ultra (Dinasti Publisher, 2025)
Personnel’s competence and motivation are phenomena in organizational management, including in the military environment. This study aims to analyze competence and motivation of personnel in improving their performance in a military institution in Indonesia. This study adopts qualitative method with factor analysis. Respondents interviewed in this study were five informants selected by purposive sampling method, i.e. selecting respondents who were considered to have knowledge about the problems to be studied and supported by observation and documentation. The data processing and analysis model of this study is based on the interactive model of Miles, Huberman and Saldana. The results of the study show that: (1) personnel’ competence in the service organization of a military institution can be influenced by training, work experience, ability, placement and work facilities; (2) personnel’s motivation is influenced by appreciation/award, attitude, comfortable work environment, welfare, role and responsibility factors; (3) competence and motivation are factors that drive performance improvement.